2020
DOI: 10.1126/science.abb3153
|View full text |Cite
|
Sign up to set email alerts
|

Building social cohesion between Christians and Muslims through soccer in post-ISIS Iraq

Abstract: Can intergroup contact build social cohesion after war? I randomly assigned Iraqi Christians displaced by the Islamic State of Iraq and Syria (ISIS) to an all-Christian soccer team or to a team mixed with Muslims. The intervention improved behaviors toward Muslim peers: Christians with Muslim teammates were more likely to vote for a Muslim (not on their team) to receive a sportsmanship award, register for a mixed team next season, and train with Muslims 6 months after the intervention. The intervention did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
152
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(182 citation statements)
references
References 43 publications
6
152
1
Order By: Relevance
“…In such situations, cross-cutting identities may be useful avenues to engender affinity. In the realm of sports, others have suggested that teams or clubs can be a useful cross-cutting tie to highlight and playing sports with out-group members can improve certain behaviors and attitudes toward them (Alrababa'h et al, 2019;Dawes & Rubenson, 2020;Lowe, 2021;Mousa, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such situations, cross-cutting identities may be useful avenues to engender affinity. In the realm of sports, others have suggested that teams or clubs can be a useful cross-cutting tie to highlight and playing sports with out-group members can improve certain behaviors and attitudes toward them (Alrababa'h et al, 2019;Dawes & Rubenson, 2020;Lowe, 2021;Mousa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This paper adds to the growing number of studies using sports to explore dynamics of intergroup relations. Some researchers vary "contact" with outgroup members through sports activities to measure the effect of sportsrelated cooperation on attitudes and behaviors (Lowe, 2021;Mousa, 2020). Other studies consider how sports team "fandom" generates cross-cutting, potentially unifying identities (Dawes & Rubenson, 2020) and how celebrity players of diverse backgrounds can help reduce prejudice (Alrababa'h et al, 2019).…”
Section: Nationalism Sports and Intergroup Relationsmentioning
confidence: 99%
“…Masculinity predicts CTs through increased competitiveness, specific interventions focusing on increasing social cohesion -such as promoting group activities and intergroup contact (Pagotto, Visintin, De Iorio, & Voci, 2013;Mousa, 2020) -or prosocial traits among the target public might indirectly affect CTs.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several experimental studies conducted in the laboratory manipulated direct contact but are unlikely to generalize to real‐world settings (e.g., Mendoza‐Denton & Page‐Gould, 2008) and few studies have manipulated direct contact in the field. Realizing meaningful manipulations in real‐world contexts is difficult and, when it is done, results may be weaker than those obtained in the laboratory (Moussa, 2020). The generalizability of findings obtained with experimental procedures in the laboratory is limited and also impacts the likelihood of realistically implementing direct contact (see Blascovich et al., 2002, for a discussion of more ecologically valid, laboratory‐based approaches).…”
Section: Applied Social Policy and Practice Implicationsmentioning
confidence: 99%